2014
DOI: 10.1007/s00439-014-1422-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel variant in the 3′ UTR of human SCN1A gene from a patient with Dravet syndrome decreases mRNA stability mediated by GAPDH’s binding

Abstract: Mutations in the SCN1A gene-encoding voltage-gated sodium channel α-I subunit (Nav1.1) cause various spectrum of epilepsies including Dravet syndrome (DS), a severe and intractable form. A large number of SCN1A mutations identified from the DS patients lead to the loss of function or truncation of Nav1.1 that result in a haploinsufficiency effects, indicating that the exact expression level of SCN1A should be essential to maintain normal brain function. In this study, we have identified five variants c.*1025T>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 56 publications
0
22
0
1
Order By: Relevance
“…The C1794U mutation in the 3′ UTR of SCN1A mRNA was shown to affect protein expression and mRNA stability, possibly via changes in predicted mRNA secondary structures. GAPDH was shown to selectively bind to the U‐rich mutant 3′ UTR and to negatively regulate protein expression and mRNA stability …”
Section: Gapdh–rna Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C1794U mutation in the 3′ UTR of SCN1A mRNA was shown to affect protein expression and mRNA stability, possibly via changes in predicted mRNA secondary structures. GAPDH was shown to selectively bind to the U‐rich mutant 3′ UTR and to negatively regulate protein expression and mRNA stability …”
Section: Gapdh–rna Interactionsmentioning
confidence: 99%
“…Third, GAPDH sequesters Rheb and prevents mTORc1 activation . Finally, in ketogenic diets, GAPDH may be free from glycolysis and able to destabilize the SCN1A mRNA to reduce translation of the sodium transporter NaV 1.1, and alleviate conditions linked to Dravet syndrome …”
Section: Gapdh: a Missing Link Between Rna Biogenesis And Energy Metamentioning
confidence: 99%
“…These variants are virtually always associated with severe phenotypes [8][9][10] ; 97.7% of genomic rearrangements and splice site, nonsense, and frameshift SCN1A variants are mainly associated with Dravet syndrome. 13,[17][18][19][20] Moreover, parental mosaicism for the pathogenic SCN1A variant has been well recognized in cases were mosaic parents of Dravet children show a mild epilepsy phenotype. Functional studies have shown varying degrees of loss of function through a lack of sodium current when pathogenic variants are located in critical regions of the gene (voltage sensor and/or ion-pore regions).…”
Section: Introductionmentioning
confidence: 99%
“…GAPDH-RNA binding alters mRNA stability (Bonafe et al, 2005;Ikeda et al, 2012;Zeng et al, 2014). Several reports suggest that GAPDH binding to RNA may play a role in nucleocytoplasmic transport of RNA (Singh and Green, 1993;Muller et al, 1992;Hamilton et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Three types of polynucleotide-GAPDH interaction have been described, so far: (i) GAPDH binding to RNA, mostly represented by AU-Rich Elements (ARE) in the 3'-UTR of mRNA (Nagy and Rigby, 1995;Seidler, 2013) (ii) formation of multiprotein-RNA complexes, with GAPDH and RNA being important structural components (Mazurek et al, 1996;Carlile et al, 1998) (iii) GAPDH binding to single-stranded DNA at telomeric sequences near the chromosomal ends (Sundararaj et al, 2004;Demarse et al, 2009). GAPDH-RNA binding affects mRNA stability and template activity (Bonafe et al, 2005;Rodriguez-Pascual et al, 2008;Backlund et al, 2009;Kondo et al, 2011;Ikeda et al, 2012;Zeng et al, 2014). RNA binding activity of GAPDH is attributed to the Rossmann fold which forms NAD + -binding center located at the Nterminus of GAPDH polypeptide (Rossman, 1981).…”
Section: Introductionmentioning
confidence: 99%